2-83bromo -2-deoxyglucose, 6-bromo-glucose: two Trojan horses for the war against cancer? - 3-18fluoro-pyruvate as a probe for enhanced expression of monocarboxylate transporters in cancer. Issue 3 (2019) - P, Dell'Antone
No abstract available